Production, Purification and Standardization of Anticancerous Enzyme (L-Asparaginases) from Aspergillus Niger Using Soil Samples by Solid State Fermentation - Rahiman, OM Fasalu; Mohthash, Musambil; Faris, U Salmanul; Muneersha, TK Mohammed; Shejina, M (International Journal of Applied Sciences and Biotechnology, 2014)
Biotechnology techniques can provide an unlimited and pure source of enzymes as an alternative to the harsh chemicals traditionally used in industry for accelerating chemical reactions. L-asparaginase is one among them, found in various plants, animals and bacterial cells. Lasparaginase is studied to be responsible for catalyzing the deamination of Asparagines to yield Aspartic acid and an ammonium ion, resulting in depletion of free circulatory Asparagines in plasma. Its use in therapeutics is found to be remarkable, especially for those specific cases where blood cells become cancerous, such as in acute lymphoblastic leukemia. In this study we have made an effort to isolate, identify and screen micro-organism (Aspergillus niger) for the production of anticancerous enzyme (L-asparaginases) by solid state fermentation process and the produced enzyme was purified and characterized for L-asparaginases. The aim of the study was to validate the solid fermentation process in terms of its reliability and feasibility for production of L-asparaginase enzyme. This method was found to be very cost effective and reliable when compared to the other expensive techniques used around the globe for enzyme production. Even though the product yield and purity is comparatively less in comparison with the other techniques it can be still used as a reliable technique for short scale enzyme production. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11278 Int J Appl Sci Biotechnol, Vol. 2(4): 488-492